Photovoltaic panel recycling: from type-selective processes to flexible apparatus for simultaneous treatment of different types. (1st October 2016) - Pagnanelli, F.; Moscardini, E.; Abo Atia, T.; Toro, L.
Abstract : Photovoltaic (PV) technology for renewable energy utilisation is constantly growing throughout the world. Many recent efforts were devoted to the treatment of end-of-life panels, but only two full-scale processes were developed for crystalline silicon modules (Deutsche Solar) and CdTe panels (First Solar). Furthermore, recent developments concerned with new technologies designed for treating together more kinds of PV panels by automated processes. In this work, a picture of the PV world in terms of market, typology, waste dynamics and recoverable materials was given. A description of full-scale processes will be reported evidencing products and yields of recovery. A case study of process development for the simultaneous treatment of different kinds of PV panels was presented. In particular, experimental results in lab and pilot scale were described regarding the development and optimisation of a process including both physical pre-treatment and hydrometallurgical treatment for the recovery of target metal.